The "F" in SAFE: Reliability of assessing clean faces for trachoma control in the field. - Sheila K West; Derick Ansah; Beatriz Munoz; Nicodemus Funga; Harran Mkocha (Public Library of Science (PLoS), 2017)
Although facial cleanliness is part of the SAFE strategy for trachoma there is controversy over the reliability of measuring a clean face. A child's face with no ocular and nasal discharge is clean and the endpoint of interest, regardless of the number of times it must be washed to achieve that endpoint. The issue of reliability rests on the reproducibility of graders to assess a clean face. We report the reproducibility of assessing a clean face in a field trial in Kongwa, Tanzania.Seven graders were trained to assess the presence and absence of nasal and ocular discharge on children's faces. Sixty children ages 1-7 years were recruited from a community and evaluated independently by seven graders, once and again about 50 minutes later. Intra-and inter-observer variation was calculated using unweighted kappa statistics. The average intra-observer agreement was kappa = 0.72, and the average inter-observer agreement was kappa = 0.78.Intra-observer and inter-observer agreement was substantial for the assessment of clean faces using trained Tanzania staff who represent a variety of educational backgrounds. As long as training is provided, the estimate of clean faces in children should be reliable, and reflect the effort of families to keep ocular and nasal discharge off the faces. These data suggest assessment of clean faces could be added to trachoma surveys, which already measure environmental improvements, in districts.